Effect of Reducing the Conventional Feeding Rate on Water Quality and Shrimp Production Variables in Penaeus monodon Shrimp Culture with Zero Water Exchange Model Using Molasses as Carbon Source - Pohan Panjaitan (Marine Science Department Diponegoro University, 2010)
In aquacultureparticularly for fishes culture it was shown that the application of carbon had brought about good benefits in terms of water quality, fishes production variables and increase in bacterial biomass. Moreover, bacterial biomass used to replace part of the feed requirement of fishes resulting a considerable cost saving and the boasting profit for the farmer. Therefore, the aim of this study was to evaluate the effects of reducing conventional feeding rate on water quality and shrimp production variables within Penaeus monodon shrimp culture with zero water exchange model using molasses. Study shows that using molasses with the level of C: N ratio = 20.0:1 at 75 % of conventional feeding rate is the most promising features of zero water exchange culture system because it offers increased biosecurity, reduced feed costs, waste and water use. Keywords : Feeding rate, water quality, zero water exchange model, molasses Dibudidaya perairan terutama untuk budidaya ikan telah diperlihatkan bahwa penggunaaan karbon membawa manfaat dari sisi kualitas air, produksi ikan dan peningkatan dalam biomassa bakteri. Biomassa bakteri digunakan untuk mengantikan sebagian kebutuhan makanan ikan sehingga dapat menghemat biaya dan menguntungkan bagi petani. Tujuan studi ini adalah untuk mengevaluasi pengaruh pengurangan jumlah pakan konvensional terhadap variable kualitas air dan produksi udang dalam budidaya udang Penaeus monodon dengan sistem tanpa pergantian air menggunakan molasses. Hasil penelitian menunjukkan bahwa penggunaan molasses dengan level ratio C:N = 20.0:1 dan pemberian pakan 75 % dari jumlah pakan konvensional merupakan pola yang sangat menjanjikan bagi system budidaya tanpa pergantian air sebab perlakuan tersebut dapat meningkatkan biosecurity, mengurangi biaya pakan, limbah dan penggunaan air. Kata kunci: Jumlah pakan,kualitas air,model tanpa pergantian air, molasses